Pengaruh Kepimimpinan Situasional dan Lingkungan Kerja terhadap Kinerja Karyawan pada Yayasan Memajukan Ilmu dan Kebudayaan Jakarta Barat: The Influence of Situational Leadership and Work Environment on Employee Performance at the West Jakarta Foundation for the Advancement of Science and Culture - Elsa Clarissa; Rani Rani (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
The research background highlights the importance of leadership that can adapt to situations and a conducive work environment in enhancing employee productivity and effectiveness. This study aims to examine the influence of Situational Leadership and Work Environment on Employee Performance at Yayasan Memajukan Ilmu dan Kebudayaan in West Jakarta. The research method used is quantitative associative with data collection techniques through observation, questionnaires, and documentation. The population in this study consists of all employees of the foundation, with a sample of 65 respondents selected using a saturated sampling technique. Data analysis was conducted using multiple linear regression assisted by SPSS version 28. The results show that Situational Leadership and Work Environment have both partial and simultaneous positive and significant effects on Employee Performance. The coefficient of determination (R²) value of 83.5% indicates that both variables dominantly explain Employee Performance. These findings provide recommendations for the foundation to continuously develop flexible leadership styles and create a supportive work environment to sustainably improve employee performance